2018
DOI: 10.7717/peerj.5653
|View full text |Cite
|
Sign up to set email alerts
|

New mud dragons from Svalbard: three new species ofCristaphyesand the first Arctic species ofPycnophyes(Kinorhyncha: Allomalorhagida: Pycnophyidae)

Abstract: BackgroundKinorhynchs are marine, microscopic invertebrates inhabiting the seafloors. Their segmented trunk equipped with spines and processes has inspired scientists to give them the common name “mud dragons.” Even though kinorhynchs have been known since the 19th century, less than 300 species are known to science, and it is still considered a largely understudied animal group—in particular in the Arctic, from which only 23 species are known so far.MethodsSamples were collected at eight stations around Svalb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Studies of Kinorhyncha from the deep sea have frequently reported unidentified species, mostly from the Indian, Pacific, and Atlantic Oceans (Neuhaus, 2013;Zeppilli et al, 2018). More recently, studies to the species level have received a strong boost, and up to 45 species have recently been described or reported from this environment (Neuhaus and Blasche, 2006;Sørensen, 2008a;Neuhaus and Sørensen, 2013;Sánchez et al, 2014aSánchez et al, ,b, 2019aAdrianov and Maiorova, 2015, 2016Sørensen, 2018, 2019;Sørensen and Grzelak, 2018;Sørensen et al, , 2019Yamasaki et al, 2018aYamasaki et al, ,b,c, 2019Cepeda et al, 2019a). Of these, some species seem to possess wider ranges of distribution than their congeners from the coastal zone.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Kinorhyncha from the deep sea have frequently reported unidentified species, mostly from the Indian, Pacific, and Atlantic Oceans (Neuhaus, 2013;Zeppilli et al, 2018). More recently, studies to the species level have received a strong boost, and up to 45 species have recently been described or reported from this environment (Neuhaus and Blasche, 2006;Sørensen, 2008a;Neuhaus and Sørensen, 2013;Sánchez et al, 2014aSánchez et al, ,b, 2019aAdrianov and Maiorova, 2015, 2016Sørensen, 2018, 2019;Sørensen and Grzelak, 2018;Sørensen et al, , 2019Yamasaki et al, 2018aYamasaki et al, ,b,c, 2019Cepeda et al, 2019a). Of these, some species seem to possess wider ranges of distribution than their congeners from the coastal zone.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the species Echinoderes cf. eximus and Pycnophyes ancalagon Sørensen & Grzelak, 2018, the latter recently described from the Svalbard Archipelago (Arctic Ocean), are firstly reported for the boreal area.…”
Section: Introductionmentioning
confidence: 95%
“…In the context of global change and decreasing studies of taxonomy, especially those of small-sized taxa, there is a need to improve taxonomic information about meiofaunal organisms, even in geographic areas that are supposed to be relatively well-studied (Mora et al 2011;Sørensen & Grzelak 2018). A recent sampling done in the proximities of Syd-Hällsö Island (Strömstad, Sweden) revealed a new species of Kinorhyncha from Skagerrak.…”
Section: Introductionmentioning
confidence: 99%
“…and Malakhov, 1999), C. carinatus (Zelinka, 1928), C. chukchiensis (Higgins, 1991), C. cristatus (Sánchez et al, 2013), C. cryopygus (Higgins and Kristensen, 1988), C. dordaidelosensis Sørensen and Grzelak, 2018, C. furugelmi (Adrianov, 1999in Adrianov and Malakhov, 1999, C. glaurung Sørensen andGrzelak, 2018, C. odhneri (Lang, 1949) and C. scatha Sørensen and Grzelak, 2018. Male specimens of C. nubilis (Sánchez et al, 2014) are unknown, so this species cannot be assumed to lack these tubes.…”
Section: Remarks On Diagnostic Charactersmentioning
confidence: 99%
“…Kinorhynchs, commonly known as mud dragons, are small, holobenthic, meiofaunal organisms that inhabit the spaces and crevices between the sediment particles of worldwide oceans (Neuhaus, 2013;Sørensen and Pardos, 2008). Much of the currently known biodiversity of the phylum includes intertidal to circalittoral species, biased by samplings being done in the most accessible marine areas (Neuhaus, 2013;Sørensen et al, 2018). However, many shoreline regions still remain poorly studied, as it is the case of the Caribbean Basin.…”
Section: Introductionmentioning
confidence: 99%